“The Monkeypox Fear Scale: development and initial validation in a Peruvian sample “ - Caycho‑Rodríguez, Tomás (2022)
“Background: Fear is one of the basic emotions generated during periods of infectious diseases. Therefore, the aim of this study was to develop and validate a scale that assesses monkeypox fear, the Monkeypox Fear Scale (MFS). Methods: A total of 451 Peruvians participated (61% women and 39% men), with a mean age of 28.31 years (SD=9.72). based on procedures from classical test theory (CTT) and item response theory (IRT). Classical Test Theory (CTT) and Item Response Theory (IRT) procedures were used. Results: The results showed that MFS has a two-factor structure related to emotional and physiological fear fac‑ tors (χ2=41.87; df=12; p<.001; CFI=.99; TLI=.99; RMSEA=.074 [IC90% .051–.100]). In addition, the physiological and emotional factors showed good reliability. Measurement invariance analysis showed that the factor structure of the MFS is strictly invariant between male and female groups. Finally, the discrimination and difculty parameters of the items show adequacy. In addition, the scale seems to be more accurate in measuring high levels of fear of monkeypox. Conclusion: The MFS has adequate psychometric evidence to assess fear of monkeypox in the Peruvian population. These fndings may guide future studies related to the consequences of monkeypox on mental health.“